Implementation of Good Governance Principles in BUMDes Wija Sari Samsam Village - Desak Made Mya Yudia Sari; Ida Ayu Nirma Prameswari; Ni Putu Indah Jeniari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The implementation of Good Corporate Governance principles plays a crucial role in ensuring that transparency, accountability, and sustainability are able to optimally support village economic development. The purpose of this study is to analyze in depth the implementation of Good Corporate Governance principles, including transparency and participatory, in the Wija Sari Village-Owned Enterprise in Samsam Village. This study uses a qualitative case study with an interpretive paradigm as the umbrella and research method. Qualitative observation data used include observation, interviews, and documentation using four key informants and validators. The Wija Sari Village-Owned Enterprise in Samsam Village, was chosen as the research site. The results of the study indicate that transparency and participatory characteristics can be implemented in accordance with applicable rules and procedures at the planning, implementation, and accountability in the management of the Village-Owned Enterprise, whose funding sources are transferred through village funds. Although several obstacles were found in the management process, such as limited competent human resources and balanced with digitalization to support real-time data transparency. This research is expected to be a reference for other Village-Owned Enterprises or similar institutions in optimizing the principles of Good Corporate Governance for the welfare of village communities in accordance with their objectives.